2016
DOI: 10.1590/1983-21252016v29n317rc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Irrigation Levels and Plant Density on "Second-Season" Maize

Abstract: -This study assessed the effect of different irrigation levels and plant densities on maize crops cultivated during the second season in the Western Border region of the State of Rio Grande do Sul. This work was conducted at the Federal Institute of Farroupilha -Alegrete Campus/RS -between January and June 2014. Treatments were arranged in a completely randomized 5 × 4 factorial design, with 3 replicates each. Irrigation of fixed amounts of water that were based on the evapotranspiration of the culture (Et c )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
0
2
1
2
Order By: Relevance
“…However, hybrids had a significant effect on all variables (p ≤ 0.01). These results disagree with those reported by Ben et al (2016), who reported that irrigation affected dry matter, hundred-grain weight, and the highest grain yield of the maize hybrid Dekalb 250 PRO2 maize hybrid for the 100% ETc irrigation depth. This difference may ns, *, ** -Not significant and significant at p ≤ 0,05 and p ≤ 0,01 by F test Table 4.…”
Section: Rh (%)contrasting
confidence: 99%
“…However, hybrids had a significant effect on all variables (p ≤ 0.01). These results disagree with those reported by Ben et al (2016), who reported that irrigation affected dry matter, hundred-grain weight, and the highest grain yield of the maize hybrid Dekalb 250 PRO2 maize hybrid for the 100% ETc irrigation depth. This difference may ns, *, ** -Not significant and significant at p ≤ 0,05 and p ≤ 0,01 by F test Table 4.…”
Section: Rh (%)contrasting
confidence: 99%
“…A menor média de precipitação acontece em agosto e a maior em outubro (Soares et al, 2016). Devido à variabilidade sazonal das chuvas na região da fronteira oeste do Estado, há períodos de seca que causam perdas significativas na produção agrícola (Ben et al, 2016), sendo que o município de Alegrete, segundo Maluf (2000), apresenta uma deficiência hídrica anual de 16 mm. O Solo da área do experimento é classificado como Argissolo Vermelho Eutrófico arênico, com horizonte A moderado, de textura arenosa média e relevo suave ondulado (Flores et al, 2010;Santos et al, 2013).…”
Section: Methodsunclassified
“…The Midwest of Brazil accounts for 40% of national corn production, with the state of Mato Grosso do Sul being the second-largest producer, especially the region of Grande Dourados, where it is grown mostly under rainfed conditions (Almeida et al, 2017). However, droughts in this region during sowing or ear formation have caused high corn yield losses in corn grown in offseason, making water supply suitable and advisable to reach its productive potential (Oliveira et al, 2012;Ben et al, 2016;Comas et al, 2019e Silva et al, 2019.…”
Section: Introductionmentioning
confidence: 99%